Assessment of the Effect of Clinical Rotation in Radiology on Medical Students’ Awareness Level of Ionising Radiation and Radiation - Mawya A. Khafaji; Sarah K. Hagi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Doctors’ knowledge of ionising radiation and radiation protection is vital, especially when requesting radiological investigations that involve patients exposure. A cross-sectional study conducted during the academic year 2009-2010 at Faculty of Medicine, King Abdulaziz University. The objective was to evaluate the effect of clinical rotation in radiology on medical students’ awareness of ionising radiation. A questionnaire was used to collect data from 326 of 6th year medical students post clinical rotation. Fourth year students were used as a control, representing students with no theoretical or clinical experience in radiology. One hundred sixtythree students (50%) scored around 60%, 13 (4%) scored zero and only 22 (7%) scored 85% or above. However, 6th year students scored higher than the control group in most questions with an overall mean ±SD of 51.6 ±19.7. Nearly 38% thought that objects in the room still emit radiation after completion of exposure. More than 50% of them thought that magnetic resonance imaging involves ionizing radiation. The results highlighted; students who completed their clinical rotation in radiology performed better than those who did not; over-all knowledge of ionising radiation and radiation protection is still very poor. Modification to the existing curriculum should be considered.